Pre-clinical toxicity assessment of Artemisia absinthium extract-loaded polymeric nanoparticles associated with their oral administration - Kauser, Sana; Mughees, Mohd; Swami, Sanskriti; Wajid, Saima (Frontiers in Pharmacology, 2023)
Background: This study was designed to quantify the composition of the ethanolic extract of Artemisia absinthium through gas chromatography–mass spectrometry analysis and ensure in vivo safety of A. absinthium extract-loaded polymeric nanoparticles (ANPs) before considering their application as a drug carrier via the oral route. Methods: We synthesized N-isopropylacrylamide, N-vinyl pyrrolidone, and acrylic acid crosslinked polymeric NPs by free-radical polymerization reaction and characterized them by Fourier-transform infrared spectroscopy, transmission electron microscopy, and dynamic light scattering spectroscopy. Different concentrations of extract (50 mg/kg, 300 mg/kg, and 2,000 mg/kg body weight) were encapsulated into the hydrophobic core of polymeric micelles for the assessment of acute oral toxicity and their LD50 cut-off value as per the test procedure of OECD guideline 423. Orally administered female Wistar rats were observed for general appearance, behavioral changes, and mortality for the first 30 min, 4 h, 24 h, and then, daily once for 14 days. Result: ANPs at the dose of 300 mg/kg body weight were used as an initial dose, and rats showed few short-lived signs of toxicity, with few histological alterations in the kidney and intestine. Based on these observations, the next set of rats were treated at a lower dose of 50 mg/kg and a higher dose of 2,000 mg/kg ANPs. Rats administered with 50 mg/kg ANPs remained normal throughout the study with insignificant histological disintegration; however, rats treated at 2,000 mg/kg ANPs showed some signs of toxicity followed by mortality among all three rats within 24–36 h, affecting the intestine, liver, and kidney. There were no significant differences in hematological and biochemical parameters among rats treated at 50 mg/kg and 300 mg/kg ANPs. Conclusion: We conclude that the LD50 cut-off value of these ANPs will be 500 mg/kg extract loaded in polymeric NPs.